Rancang Bangun Aplikasi Perpustakaan Berbasis Web Menggunakan YII Framework - Utami, Wiranti Sri; Nurlia, Vera; Faisal, Muhammad (UNIVERSITAS RAHARJA, 2024)
Information technology is currently very developed, as libraries already use information technology to provide information about the process of borrowing and returning books. The library is a place that is always there in every tertiary institution, where all collections of books are neatly arranged on the library bookshelves, making it easier for library visitors to find the book they want to read. This study discusses how the process of entering book data, member data, book loan data and book return data makes it easier for officers to record various information into an intelligent library application. In this study, several methods were used, namely the waterfall method as system analysis, then in system design using UML (Unified Modeling Language) as a flow diagram of a proposed system and the Black Box method as a system testing method. This intelligent library application uses the Yii Framework to develop web-based applications. The final results of this research produce a web-based intelligent library application using the Yii Framework to make it easier for officers to store data, manage data and display the required information easier and faster.